VIRTUAL TOUR: TOURISM COMMUNICATION MEDIA DURING THE COVID-19 PANDEMIC IN INDONESIA - Irwan Irwan; Evi Novianti (Profetik: Jurnal Komunikasi, 2021)
The covid-19 outbreak that currently hits Indonesia and the world has remained the community to be active to anticipate the spread of this virus. This condition certainly has an impact on tourism destinations and also stakeholders in the tourism sector with no tourist visits in the destination. To face these conditions related to The Covid-19 pandemic, tourism actors must start aggressively looking for new strategies to survive and rise from adversity.  Switching to digital media and making new innovations in digital use is considered to be the most suitable choice during this pandemic. One of the digital innovations that can be made by tourism actors is creating a virtual tour. Virtual tours provide the sensation of traveling for tourists without having to leave the house so that they can prevent the spread of this virus. By using a qualitative descriptive method, this research is a phenomenological study that tries to find out about the perceptions of these virtual tourists in experiencing the virtual tour as a tourism communication medium during the Covid-19 pandemic in Indonesia. As a result, even though they cannot feel the sensation and satisfaction of carrying out real tourism activities, virtual tour phenomena activities are quite enough to foster people's to be able to travel again when the conditions are back to normal.